2021
DOI: 10.5501/wjv.v10.i4.182
|View full text |Cite
|
Sign up to set email alerts
|

Current systematic reviews and meta-analyses of COVID-19

Abstract: BACKGROUND Coronavirus disease 2019 (COVID-19) has left a significant impact on the world's health, economic and political systems; as of November 20, 2020, more than 57 million people have been infected worldwide, with over 1.3 million deaths. While the global spotlight is currently focused on combating this pandemic through means ranging from finding a treatment among existing therapeutic agents to inventing a vaccine that can aid in halting the further loss of life. AIM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 137 publications
0
17
0
Order By: Relevance
“…The higher the dose of steroid therapy, the higher the risk of developing steroid-induced diabetes. The use of steroids in diabetic patients increases the risk of hospitalization due to uncontrolled blood sugar [ 64 ].…”
Section: Dipeptidyl Peptidase 4 (Dpp-4) Inhibitorsmentioning
confidence: 99%
“…The higher the dose of steroid therapy, the higher the risk of developing steroid-induced diabetes. The use of steroids in diabetic patients increases the risk of hospitalization due to uncontrolled blood sugar [ 64 ].…”
Section: Dipeptidyl Peptidase 4 (Dpp-4) Inhibitorsmentioning
confidence: 99%
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram is reported in Figure 1 . After the full texts were scrutinized against the inclusion and exclusion criteria, 29 SRs were included in the umbrella review [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and 23 SRs were excluded [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%
“…After the full texts were scrutinized against the inclusion and exclusion criteria, 29 SRs were included in the umbrella review [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and 23 SRs were excluded [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Reasons for exclusion were: SRs not covering or with no informative data on CP therapy...…”
Section: Resultsmentioning
confidence: 99%
“…Sleep apnea was one of the differential diagnoses for altering mental status; consequently, outpatient sleep testing was scheduled. Nausea and vomiting could be signs of COVID-19 infection [ 5 ]. The patient had not received the COVID-19 vaccination.…”
Section: Case Presentationmentioning
confidence: 99%